In the Barrios : Latinos and the Underclass Debate - Pinderhughes, Raquel; Moore, Joan W. (Book collections on Project MUSE., 1993)
The image of the "underclass" framed by persistent poverty, long-term joblessness, school dropout, teenage pregnancy, and drug use, has become synonymous with urban poverty. But does this image tell us enough about how the diverse minorities among the urban poor actually experience and cope with poverty? No, say the contributors to In the Barrios. Their portraits of eight Latino communities - in New York, Los Angeles, Miami, Houston, Chicago, Albuquerque, Laredo, and Tucson - reveal a far more complex reality. In the Barrios responds directly to current debates on the origins of the "underclass" and depicts the cultural, demographic, and historical forces that have shaped poor Latino communities. These neighborhoods share many hardships, yet they manifest no "typical" form of poverty. Instead, each group adapts its own cultural and social resources to the difficult economic circumstances of American urban life. Mexican Americans in Tucson are among the poorest people in the country, yet bolstered by strong extended families and affordable local housing, many own their own homes. In a Puerto Rican neighborhood in Brooklyn, displaced workers are suffering severely, but they live side by side with working-class homeowners who are contributing substantially to the institutional viability of the community. In the Barrios challenges the image of isolation and decay that is so often portrayed in theories of urban poverty. The contributors explore the network of economic and emotional support that many Latino neighborhoods share across families and borders, strengthening their collective ability to cope. While underclass theories stress the loss of manufacturing jobs as a cause of persistent hardship, In the Barrios illustrates the importance of Latino employment in small community-serving businesses and in off-the-books enterprises such as street vending. New immigrants concentrate in definable areas, building a local economy that provides affordable amenities and at the same time promotes ethnic institutional development. This immigration, the editors argue, is an issue of overriding importance in understanding not only Latino poverty but American urban poverty in general. The first major assessment of inner-city Latino communities in the United States, In the Barrios will change the way we approach the current debate on urban poverty, immigration, and the underclass